Electricity storage device binder aqueous solution, electricity storage device slurry, electricity storage device electrode, electricity storage device separator, electricity storage device separator / electrode laminate, and electricity storage device

By using a water-soluble polymer of a specific composition, an excellent binder aqueous solution for power storage equipment is prepared, which solves the problems of insufficient coating, dispersion and hygroscopicity of the binder aqueous solution in the prior art, and achieves higher equipment performance and reliability.

CN119678269APending Publication Date: 2025-03-21ARAKAWA CHEM IND LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380058191.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-28
Filing Date
2023-08-08
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art is difficult to provide an aqueous solution of the power storage equipment adhesive that is excellent in coating, dispersibility and low hygroscopicity.

Method used

Excellent aqueous solution of electrical storage equipment adhesive is prepared by using specific water-soluble polymers, including (meth)acrylamide units, alkyl (meth)acrylamide units, multifunctional monomer units and unsaturated hydrocarbon sulfonic acid units.

Benefits of technology

The excellent coating, dispersion and low hygroscopicity of the adhesive aqueous solution of the power storage equipment are achieved, and the performance and reliability of the equipment are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005263142400000081
    Figure BDA0005263142400000081
  • Figure BDA0005263142400000351
    Figure BDA0005263142400000351
  • Figure BDA0005263142400000361
    Figure BDA0005263142400000361
Patent Text Reader

Abstract

An aqueous binder solution for a power storage device, the aqueous binder solution comprising a water-soluble polymer comprising 10-99.85 mol% of a (meth) (meth) acrylamide unit, an alkyl (meth) acrylamide unit and / or N, N-dimethylformamide unit, and a polymer comprising 10-99.85 mol% of a (meth) (meth) acrylamide unit and / or N, N-dimethylformamide unit. 0.001 to 20 mol% of N, N '-methylenebis ((meth) acrylamide); and 0.001 to 2.0 mol% of an unsaturated hydrocarbon sulfonic acid unit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an aqueous solution of an electric storage device binder, an electric storage device slurry, an electric storage device electrode, an electric storage device separator, an electric storage device separator / electrode laminate, and an electric storage device. Background Art

[0002] The applicant is studying a method of using a water-soluble polymer as a binder for an electrical storage device. Prior art literature Patent Literature

[0003] [Patent Document 1] Japanese Patent Application Publication No. 2018-006333 Summary of the invention Technical problem to be solved by the invention

[0004] The problem to be solved by the present invention is to provide an aqueous solution of a binder for electrical storage devices having excellent coating properties, dispersibility, and low hygroscopicity. Technical means of solving problems

[0005] The present inventors have found that the above-mentioned problems can be solved by using specific components.

[0006] According to the present disclosure, the following items are provided. (Project A1) An aqueous solution of an adhesive for an electrical storage device, The electrical storage device binder aqueous solution contains a water-soluble polymer, The water-soluble polymer comprises 10 mol% to 99.85 mol% of (meth)acrylamide units, 0.001 mol% to 20 mol% of alkyl (meth)acrylamide units and / or multifunctional monomer units, and 0.001 mol% to 2.0 mol% of unsaturated hydrocarbon sulfonic acid units. (Item B1) An aqueous solution of an adhesive for an electrical storage device, The electrical storage device binder aqueous solution contains a water-soluble polymer, The water-soluble polymer comprises (meth)acrylamide units, For the water-soluble polymer, the value calculated by Formula 1 is 2.8 or more, Formula 1: (Mw / Mn)×(Mw / Rw)×10 -4 Wherein, Mw is the weight average molecular weight, Mn is the number average molecular weight, and Rw is the average inertia radius. (Project C1) An aqueous solution of an adhesive for an electrical storage device, The electrical storage device binder aqueous solution contains a water-soluble polymer, The water-soluble polymer comprises (meth)acrylamide units, For the following vertical axis and horizontal axis, the slope of the linear function obtained by the least square method is 0.25 or less, and the intercept is 1.2 or more. The vertical axis is the common logarithm of the viscosity (mPa·s) of the aqueous solution of the storage device binder. Horizontal axis: non-volatile content (%) of the aqueous solution of the electrical storage device binder. (Project A2) A slurry for an electric storage device, The electrical storage device slurry comprises a water-soluble polymer and water, The water-soluble polymer comprises 10 mol% to 99.85 mol% of (meth)acrylamide units, 0.001 mol% to 20 mol% of alkyl (meth)acrylamide units and / or multifunctional monomer units, and 0.001 mol% to 2.0 mol% of unsaturated hydrocarbon sulfonic acid units. (Item B2) A slurry for an electric storage device, The electrical storage device slurry comprises a water-soluble polymer and water, The water-soluble polymer comprises (meth)acrylamide units, For the water-soluble polymer, the value calculated by Formula 1 is 2.8 or more, Formula 1: (Mw / Mn)×(Mw / Rw)×10 -4 Wherein, Mw is the weight average molecular weight, Mn is the number average molecular weight, and Rw is the average inertia radius. (Project C2) A slurry for an electric storage device, The electrical storage device slurry comprises a water-soluble polymer and water, The water-soluble polymer comprises (meth)acrylamide units, For the following vertical axis and horizontal axis, the slope of the linear function obtained by the least square method is less than 0.25, and the intercept is greater than 1.2. The vertical axis is the common logarithm of the viscosity (mPa·s) of the aqueous solution of the water-soluble polymer. Horizontal axis: non-volatile content (%) of the aqueous solution of the water-soluble polymer. (Item 3) The electrical storage device slurry described in the above item contains an electrode active material. (Item 4) The electrical storage device slurry described in the above item contains non-conductive particles. (Item 5) An electric storage device electrode comprising a dried product of the electric storage device slurry according to any one of the above items on a current collector. (Item 6) An electric storage device separator comprising a dried product of the electric storage device slurry according to any one of the above items on a substrate. (Item 7) An electric storage device separator / electrode laminate having a dried product of the electric storage device slurry according to any one of the above items on the active material side of the electrode. (Item 8) An electric storage device comprises the electric storage device electrode described in the above item. (Item 9) An electric storage device comprises the electric storage device separator according to the above item. (Item 10) An electric storage device comprises the electric storage device separator / electrode stack according to the above item.

[0007] One or more of the features described above may also be provided in combinations other than the combinations explicitly stated. Beneficial Effects

[0008] The electrical storage device binder aqueous solution disclosed herein is excellent in coating properties, dispersibility, and low hygroscopicity. DETAILED DESCRIPTION

[0009] In the whole of the present disclosure, the range of the numerical values ​​of each physical property value, content, etc. can be set appropriately (for example, selected from the values ​​described in the following items). Specifically, with respect to the numerical value α, when A3, A2, and A1 (set as A3>A2>A1) are given as examples, the range of the numerical value α can be, for example, less than A3, less than A2, less than A3, less than A2, greater than A1, greater than A2, greater than A1, greater than A2, A1-A2 (Above A1 and below A2), A1-A3, A2-A3, greater than A1 and less than A3, greater than A1 and less than A2, greater than A2 and less than A3, greater than A1 and less than A3, greater than A1 and less than A2, greater than A2 and less than A3, greater than A1 and less than A3, greater than A1 and less than A2, greater than A2 and less than A3, greater than A1 and less than A3, greater than A1 and less than A3, greater than A2 and less than A3, greater than A1 and less than A3, greater than A1 and less than A2, greater than A2 and less than A3, greater than A1 and less than A3, greater than A1 and less than A2, greater than A2 and less than A3, greater than A1 and less than A3, greater than A1 and less than A2, greater than A2 and less than A3, etc.

[0010] As long as the problems to be solved by the present invention are solved, the components, conditions, quantities, etc. are not limited to those described in the specification.

[0011] "αβ amount (A / B)" means the β amount (α) of A relative to 100α% of B. Examples of α include mass %, mole %, and parts by mass. Examples of β amount include content and usage amount.

[0012] “γ ratio (A / B)” means the γ ratio calculated by the formula “A÷B”. Examples of the γ ratio include mass ratio and molar ratio.

[0013] In the present disclosure, "nonvolatile matter" refers to the total mass of components other than organic solvent and water. In one embodiment, "nonvolatile matter of object A" refers to the total mass of components remaining when 1 g of object A is heated at 105°C to a constant weight.

[0014] “(Meth)acrylic acid” means “at least one selected from the group consisting of acrylic acid and methacrylic acid”. “(Meth)acrylate” means “at least one selected from the group consisting of acrylate and methacrylate”. “(Meth)acryloyl” means “at least one selected from the group consisting of acryloyl and methacryloyl”.

[0015] Examples of the alkyl group include a linear alkyl group, a branched alkyl group, and a cycloalkyl group.

[0016] Examples of the straight-chain alkyl group include methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, and n-decyl.

[0017] The "branched alkyl group" refers to a group in which at least one hydrogen atom of a linear alkyl group is substituted with an alkyl group and the group does not have a ring structure.

[0018] Examples of the branched alkyl group include isopropyl, diethylpentyl, trimethylbutyl, trimethylpentyl, and trimethylhexyl.

[0019] Examples of the cycloalkyl group include a monocyclic cycloalkyl group, a bridged ring cycloalkyl group, a condensed ring cycloalkyl group, etc. Furthermore, a group in which at least one hydrogen atom of a cycloalkyl group is substituted by an alkyl group is also considered to be a cycloalkyl group.

[0020] "Single ring" refers to a ring structure formed by covalent bonds of carbon and without a bridge structure inside. "Fused ring" refers to a ring structure in which two or more single rings share two atoms (i.e., only one side of each ring is shared (fused) with each other). "Bridged ring" refers to a ring structure in which two or more single rings share three or more atoms.

[0021] Examples of the monocyclic cycloalkyl group include cyclopentyl, cyclohexyl, cycloheptyl, cyclodecyl, and 3,5,5-trimethylcyclohexyl.

[0022] Examples of the bridged cycloalkyl group include tricyclodecanyl, adamantyl, and norbornyl.

[0023] In addition, the alkyl group also includes a group in which a linear alkyl group, a branched alkyl group, and a cycloalkyl group are combined. Examples of such a group in which a linear alkyl group, a branched alkyl group, and a cycloalkyl group are combined include a cycloalkylalkyl group and the like.

[0024] Examples of the salt include inorganic salts and organic salts.

[0025] "Inorganic salt" refers to a salt wherein the cationic portion is a metal cation.

[0026] Examples of the inorganic salt include sodium salt, lithium salt, calcium salt and the like.

[0027] Examples of the organic salt include ammonium salts and amine salts.

[0028] [Electric storage device binder aqueous solution: aqueous solution] The present invention relates to an aqueous solution of an electrical storage device binder. The electrical storage device binder aqueous solution contains a water-soluble polymer, The water-soluble polymer comprises 10 mol% to 99.85 mol% of (meth)acrylamide units, 0.001 mol% to 20 mol% of alkyl (meth)acrylamide units and / or multifunctional monomer units, and 0.001 mol% to 2.0 mol% of unsaturated hydrocarbon sulfonic acid units.

[0029] <Water-soluble polymer: polymer> The water-soluble polymers may be used alone or in combination of two or more.

[0030] The term "water-soluble" means that when 0.5 g of the compound is dissolved in 100 g of water at 25°C, the water-insoluble component is less than 0.5% by mass (less than 2.5 mg).

[0031] Examples of the water-insoluble component include less than 0.5 mass %, less than 0.4 mass %, less than 0.3 mass %, less than 0.2 mass %, less than 0.1 mass %, and 0 mass %.

[0032] ((Meth)acrylamide) The (meth)acrylamide may be used alone or in combination of two or more.

[0033] The mole % content ((meth)acrylamide unit / water-soluble polymer) includes, for example, 99.85 mol%, 99.8 mol%, 99.6 mol%, 99.5 mol%, 99.2 mol%, 99 mol%, 95 mol%, 90 mol%, 85 mol%, 80 mol%, 75 mol%, 70 mol%, 65 mol%, 60 mol%, 55 mol%, 50 mol%, 45 mol%, 40 mol%, 35 mol%, 30 mol%, 25 mol%, 20 mol%, 15 mol%, 10 mol%, 9 mol%, 5 mol%, 4 mol%, 2 mol%, 1 mol%, etc. In one embodiment, the content is preferably 1 mol% to 99.85 mol%, more preferably 10 mol% to 99.6 mol%, and further preferably 20 mol% to 99 mol%.

[0034] The mass% content ((meth)acrylamide unit / water-soluble polymer) includes, for example, 99.998 mass%, 99.99 mass%, 95 mass%, 90 mass%, 85 mass%, 80 mass%, 75 mass%, 70 mass%, 65 mass%, 60 mass%, 55 mass%, 50 mass%, 45 mass%, 40 mass%, 35 mass%, 30 mass%, 25 mass%, 20 mass%, 15 mass%, 10 mass%, 9 mass%, 5 mass%, 4 mass%, 2 mass%, 1 mass%, etc. In one embodiment, the content preferably includes 1 mass% to 99.998 mass%, more preferably 10 mass% to 99.9 mass%, and further preferably 20 mass% or more and less than 99 mass%.

[0035] (Alkyl (meth) acrylamide unit) The alkyl(meth)acrylamide may be used alone or in combination of two or more.

[0036] “Alkyl (meth)acrylamide” refers to a compound in which one or more hydrogen atoms directly bonded to a nitrogen atom of (meth)acrylamide are substituted with an unsubstituted alkyl group.

[0037] Examples of the alkyl (meth)acrylamide include dialkyl (meth)acrylamide and monoalkyl (meth)acrylamide.

[0038] “Monoalkyl (meth)acrylamide” refers to a compound in which one hydrogen atom directly bonded to the nitrogen atom of (meth)acrylamide is substituted with an unsubstituted alkyl group.

[0039] Examples of the monoalkyl (meth)acrylamide include N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, and N-propyl (meth)acrylamide.

[0040] “Dialkyl (meth)acrylamide” refers to a compound in which two hydrogen atoms directly bonded to the nitrogen atom of (meth)acrylamide are substituted with unsubstituted alkyl groups.

[0041] Examples of the dialkyl (meth)acrylamide include N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, and N,N-dipropyl (meth)acrylamide.

[0042] The mol% content (alkyl (meth) acrylamide unit / water-soluble polymer) is, for example, 20 mol%, 19 mol%, 17 mol%, 15 mol%, 13 mol%, 11 mol%, 10 mol%, 9 mol%, 7 mol%, 5 mol%, 4 mol%, 2 mol%, 1 mol%, 0.9 mol%, 0.7 mol%, 0.5 mol%, 0.45 mol%, 0.4 mol%, 0.35 mol%, 0.3 mol%, 0.25 mol%, 0.20 mol%, 0.15 mol%, 0.10 mol%, 0.08 mol%, 0.06 mol%, 0.05 mol%, 0.03 mol%, 0.01 mol%, 0.009 mol%, 0.007 mol%, 0.005 mol%, 0.003 mol%, 0.001 mol%, 0 mol%, etc. In one embodiment, the content is preferably 0 mol % to 20 mol %, more preferably 0.001 mol % or more and less than 5 mol %, and further preferably 0.001 mol % to 1 mol %.

[0043] The mass% content (alkyl (meth) acrylamide unit / water-soluble polymer) is, for example, 20 mass%, 19 mass%, 17 mass%, 15 mass%, 13 mass%, 11 mass%, 10 mass%, 9 mass%, 7 mass%, 5 mass%, 4 mass%, 2 mass%, 1 mass%, 0.9 mass%, 0.7 mass%, 0.5 mass%, 0.45 mass%, 0.4 mass%, 0.35 mass%, 0.3 mass%, 0.25 mass%, 0.20 mass%, 0.15 mass%, 0.10 mass%, 0.08 mass%, 0.06 mass%, 0.05 mass%, 0.03 mass%, 0.01 mass%, 0.009 mass%, 0.007 mass%, 0.005 mass%, 0.003 mass%, 0.001 mass%, 0 mass%, etc. In one embodiment, the content is preferably 0% by mass to 20% by mass, more preferably 0.001% by mass or more and less than 5% by mass, and further preferably 0.001% by mass to 1% by mass.

[0044] (unsaturated hydrocarbon sulfonic acid and / or its salt unit) The unsaturated hydrocarbon sulfonic acid and / or its salt may be used alone or in combination of two or more.

[0045] The "unsaturated hydrocarbon sulfonic acid" refers to a sulfonic acid whose structure other than the sulfonic acid (salt) group is composed only of carbon atoms and hydrogen atoms.

[0046] Examples of the unsaturated hydrocarbon sulfonic acid or its salt include vinyl sulfonic acid, styrene sulfonic acid, (meth)allyl sulfonic acid, sodium vinyl sulfonate, sodium styrene sulfonate, sodium (meth)allyl sulfonate, and the like.

[0047] The mol% content (unsaturated hydrocarbon sulfonic acid and / or its salt unit / water-soluble polymer) is, for example, 2.0 mol%, 1.95 mol%, 1.9 mol%, 1.85 mol%, 1.8 mol%, 1.75 mol%, 1.7 mol%, 1.65 mol%, 1.6 mol%, 1.55 mol%, 1.5 mol%, 1.45 mol%, 1.4 mol%, 1.35 mol%, 1.3 mol%, 1.25 mol%, 1.20 mol%, 1.15 mol%, 1.10 mol%, 1.05 mol%, 1.0 mol%, 0.95 mol%, 0.9 mol%, 0. %. In one embodiment, the content is preferably 0.001 mol% to 2.0 mol%, more preferably 0.001 mol% to 1.5 mol%, and further preferably 0.001 mol% to 1.0 mol%.

[0048] The mass% content (unsaturated hydrocarbon sulfonic acid and / or its salt unit / water-soluble polymer) is, for example, 2.0 mass%, 1.95 mass%, 1.9 mass%, 1.85 mass%, 1.8 mass%, 1.75 mass%, 1.7 mass%, 1.65 mass%, 1.6 mass%, 1.55 mass%, 1.5 mass%, 1.45 mass%, 1.4 mass%, 1.35 mass%, 1.3 mass%, 1.25 mass%, 1.20 mass%, 1.15 mass%, 1.10 mass%, 1.05 mass%, 1.0 mass%, 0.95 mass%, 0.9 mass%, 0.10 mass%, 0.15 mass%, 0.10 ... %. In one embodiment, the content is preferably 0.001% to 1.0% by mass, more preferably 0.001% to 0.5% by mass, and further preferably 0.001% to 0.1% by mass.

[0049] The neutralization rate [unsaturated hydrocarbon sulfonate unit mass / (unsaturated hydrocarbon sulfonate unit mass+unsaturated hydrocarbon sulfonic acid unit mass)] includes, for example, 100%, 95%, 90%, 85%, 80%, 75%, 70%, 65%, 60%, 55%, 50%, 45%, 40%, 35%, 30%, 25%, 20%, 15%, 10%, etc. In one embodiment, the neutralization rate is preferably 10% to 100%.

[0050] (Multifunctional monomer unit) In one embodiment, the water-soluble polymer may optionally include a multifunctional monomer unit. The multifunctional monomer may be used alone or in combination of two or more.

[0051] The "polyfunctional monomer" refers to a monomer having two or more ethylenically unsaturated double bonds.

[0052] Examples of the polyfunctional monomer include polyfunctional (meth)acrylamide compounds, tri(allyl)-containing monomers, and triazine containing tri((meth)acryloyl) groups.

[0053] The "polyfunctional (meth)acrylamide compound" refers to a compound having two or more (meth)acrylamide groups. [Chemistry 1] (Where R 1 is a hydrogen atom or a methyl group. )

[0054] Examples of the polyfunctional (meth)acrylamide compound include N,N'-methylenebis(meth)acrylamide, N,N'-ethylenebis(meth)acrylamide, N-[tris(3-(meth)acrylamidepropoxymethyl)methyl](meth)acrylamide, N,N-bis(2-(meth)acrylamideethyl)(meth)acrylamide, N,N-[oxybis(2,1-ethylenedioxy-3,1-propylenediyl)]bis(meth)acrylamide, and N,N-1,2-ethylenediylbis{N-[2-((meth)acrylamide)ethyl](meth)acrylamide}.

[0055] Examples of the tri(allyl) group-containing monomer include triallyl isocyanurate, triallyl trimellitate, triallylamine, and triallyl(meth)acrylamide.

[0056] Examples of the triazine containing a tri((meth)acryloyl group) include 1,3,5-tri((meth)acryloyl)-1,3,5-triazine and 1,3,5-tri((meth)acryloyl)hexahydro-1,3,5-triazine.

[0057] The mole % content (multifunctional monomer unit / water-soluble polymer) includes, for example, 10 mol%, 9 mol%, 8 mol%, 7 mol%, 6 mol%, 5 mol%, 4 mol%, 3 mol%, 2 mol%, 1 mol%, 0.9 mol%, 0.7 mol%, 0.5 mol%, 0.3 mol%, 0.1 mol%, 0.05 mol%, 0.01 mol%, 0 mol%, etc. In one embodiment, the content is preferably 0 mol% to 10 mol%, more preferably 0.01 mol% to 2 mol%, and further preferably 0.05 mol% to 2 mol%.

[0058] The mass % content (multifunctional monomer unit / water-soluble polymer) includes, for example, 10 mass %, 9 mass %, 8 mass %, 7 mass %, 6 mass %, 5 mass %, 4 mass %, 3 mass %, 2 mass %, 1 mass %, 0.9 mass %, 0.7 mass %, 0.5 mass %, 0.3 mass %, 0.1 mass %, 0.05 mass %, 0.01 mass %, 0 mass %, etc. In one embodiment, the content is preferably 0 mass % to 10 mass %, more preferably 0.01 mass % to 2 mass %, and further preferably 0.05 mass % to 2 mass %.

[0059] (unsaturated carboxylic acid and / or its salt unit) In one embodiment, the water-soluble polymer may optionally contain an unsaturated carboxylic acid and / or a salt thereof unit. The unsaturated carboxylic acid and / or a salt thereof may be used alone or in combination of two or more.

[0060] Examples of the unsaturated carboxylic acid or its salt include (meth)acrylic acid, crotonic acid, maleic acid, fumaric acid, itaconic acid, sodium (meth)acrylate, sodium crotonate, sodium maleate, sodium fumarate, sodium itaconate, lithium (meth)acrylate, lithium crotonate, lithium maleate, lithium fumarate, lithium itaconate, ammonium (meth)acrylate, ammonium crotonate, ammonium maleate, ammonium fumarate, and ammonium itaconate.

[0061] The mole % content (unsaturated carboxylic acid and / or its salt unit / water-soluble polymer) includes, for example, 40 mol%, 35 mol%, 30 mol%, 25 mol%, 20 mol%, 15 mol%, 10 mol%, 5 mol%, 4 mol%, 2 mol%, 1 mol%, 0 mol%, etc. In one embodiment, the content is preferably 0 mol% to 40 mol%.

[0062] The mass % content (unsaturated carboxylic acid and / or its salt unit / water-soluble polymer) includes, for example, 30 mass %, 29 mass %, 25 mass %, 20 mass %, 15 mass %, 10 mass %, 9 mass %, 5 mass %, 4 mass %, 2 mass %, 1 mass %, 0 mass %, etc. In one embodiment, the content is preferably 0 mass % to 30 mass %, more preferably 0 mass % to 25 mass %.

[0063] Neutralization rate [unsaturated carboxylate unit mass / (unsaturated carboxylate unit mass+unsaturated carboxylic acid unit mass)] includes, for example, 90%, 85%, 80%, 75%, 70%, 65%, 60%, 55%, 50%, 45%, 40%, 35%, 30%, 25%, 20%, 15%, 10%, etc. In one embodiment, the neutralization rate is preferably 10% to 90%.

[0064] (α,β-unsaturated nitrile unit) In one embodiment, the water-soluble polymer may optionally contain an α,β-unsaturated nitrile unit. The α,β-unsaturated nitrile may be used alone or in combination of two or more.

[0065] Examples of the α,β-unsaturated nitrile include (meth)acrylonitrile, α-chloro(meth)acrylonitrile, α-ethyl(meth)acrylonitrile, and vinylidene cyanide.

[0066] Examples of the mole % content (α,β-unsaturated nitrile unit / water-soluble polymer) include 40 mol%, 35 mol%, 30 mol%, 25 mol%, 20 mol%, 15 mol%, 10 mol%, 9 mol%, 5 mol%, 4 mol%, 2 mol%, 1 mol%, 0 mol%, etc. In one embodiment, the content is preferably 0 mol% to 40 mol%.

[0067] Examples of the mass % content (α,β-unsaturated nitrile unit / water-soluble polymer) include 30 mass %, 25 mass %, 20 mass %, 15 mass %, 10 mass %, 9 mass %, 5 mass %, 4 mass %, 2 mass %, 1 mass %, 0 mass %, etc. In one embodiment, the content is preferably 0 mass % to 30 mass %.

[0068] (Alkoxyalkyl (meth)acrylate unit) In one embodiment, the water-soluble polymer may optionally include an alkoxyalkyl(meth)acrylate unit. The alkoxyalkyl(meth)acrylate may be used alone or in combination of two or more.

[0069] Examples of the alkoxyalkyl (meth)acrylate include methoxymethyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 1-methoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 2-methoxypropyl (meth)acrylate, 1-methoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, 2-methoxybutyl (meth)acrylate, 1-methoxybutyl (meth)acrylate, ethoxymethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 1-ethoxyethyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 2-ethoxypropyl (meth)acrylate, 1-ethoxypropyl (meth)acrylate, propoxymethyl (meth)acrylate, 2-propoxyethyl (meth)acrylate, 1-propoxyethyl (meth)acrylate, and butoxymethyl (meth)acrylate.

[0070] Examples of the mole % content (alkoxyalkyl (meth)acrylate unit / water-soluble polymer) include 40 mol %, 35 mol %, 30 mol %, 25 mol %, 20 mol %, 15 mol %, 10 mol %, 9 mol %, 5 mol %, 4 mol %, 2 mol %, 1 mol %, 0 mol %, etc. In one embodiment, the content is preferably 0 mol % to 40 mol %.

[0071] The mass % content ((meth) alkoxyalkyl acrylate unit / water-soluble polymer) includes, for example, 60 mass %, 55 mass %, 50 mass %, 45 mass %, 40 mass %, 35 mass %, 30 mass %, 25 mass %, 20 mass %, 15 mass %, 10 mass %, 9 mass %, 5 mass %, 4 mass %, 2 mass %, 1 mass %, 0 mass %, etc. In one embodiment, the content is preferably 0 mass % to 60 mass %.

[0072] (Monomer units that are not any of the above: other component units) The water-soluble polymer may optionally contain monomer (other component) units other than (meth)acrylamide, alkyl (meth)acrylamide, unsaturated hydrocarbon sulfonic acid and / or its salt, unsaturated carboxylic acid and / or its salt, polyfunctional monomer, α,β-unsaturated nitrile. Other components may be used alone or in combination of two or more.

[0073] Examples of other components include unsaturated phosphoric acid and / or its salt, hydroxyl group-containing (meth)acrylate, hydroxyl group-free (meth)acrylate, conjugated diene, aromatic vinyl compound, unsaturated non-hydrocarbon sulfonic acid and / or its salt.

[0074] Examples of the unsaturated phosphoric acid include vinylphosphonic acid, vinyl phosphate, bis((meth)acryloyloxyethyl)phosphate, diphenyl-2-(meth)acryloyloxyethyl phosphate, dibutyl-2-(meth)acryloyloxyethyl phosphate, dioctyl-2-(meth)acryloyloxyethyl phosphate, monomethyl-2-(meth)acryloyloxyethyl phosphate, and 3-(meth)acryloyloxy-2-hydroxypropane phosphate.

[0075] Examples of the hydroxyl group-containing (meth)acrylate include hydroxyl group-containing linear (meth)acrylate and hydroxyl group-containing branched (meth)acrylate.

[0076] Examples of the hydroxyl group-containing linear (meth)acrylate include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate.

[0077] Examples of the hydroxyl-containing branched (meth)acrylate include 1-hydroxyethyl (meth)acrylate, 1-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxy-1-methylethyl (meth)acrylate, 1-hydroxy-2-methylethyl (meth)acrylate, 1-hydroxybutyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 1-hydroxy-1-methyl-propyl (meth)acrylate, 2-hydroxy-1-methyl-propyl (meth)acrylate, 3-hydroxy-1-methyl-propyl (meth)acrylate, 1-ethyl-2-hydroxyethyl (meth)acrylate, 1-hydroxy-2-methyl-propyl (meth)acrylate, 2-hydroxy-2-methyl-propyl (meth)acrylate, 3-hydroxy-2-methyl-propyl (meth)acrylate, and 1,1-dimethyl-2-hydroxyethyl (meth)acrylate.

[0078] Examples of the (meth)acrylate not containing a hydroxyl group include linear (meth)acrylate not containing a hydroxyl group, branched (meth)acrylate not containing a hydroxyl group, alicyclic (meth)acrylate not containing a hydroxyl group, and substituted (meth)acrylate not containing a hydroxyl group.

[0079] Examples of the linear (meth)acrylate not containing a hydroxyl group include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, hexyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, and decyl (meth)acrylate.

[0080] Examples of the branched (meth)acrylate not containing a hydroxyl group include isopropyl (meth)acrylate, isobutyl (meth)acrylate, isoamyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate.

[0081] Examples of the alicyclic (meth)acrylate not containing a hydroxyl group include cyclohexyl (meth)acrylate and the like.

[0082] Examples of the conjugated diene include 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, substituted straight-chain conjugated pentadiene, and substituted conjugated hexadiene having a side chain.

[0083] Examples of the aromatic vinyl compound include styrene, α-methylstyrene, p-methylstyrene, vinyltoluene, chlorostyrene, and divinylbenzene.

[0084] Examples of the unsaturated non-hydrocarbon sulfonic acid include (meth)acrylamide tert-butyl sulfonic acid and the like.

[0085] The mass % content (other component units / water-soluble polymer) includes, for example, less than 10 mass %, less than 9 mass %, less than 7 mass %, less than 5 mass %, less than 4 mass %, less than 2 mass %, less than 1 mass %, less than 0.9 mass %, less than 0.7 mass %, less than 0.5 mass %, less than 0.4 mass %, less than 0.2 mass %, less than 0.1 mass %, 0 mass %, etc. In one embodiment, the content is preferably less than 10 mass %, more preferably less than 5 mass %, further preferably less than 1 mass %, and particularly preferably 0 mass %.

[0086] The mole % content (other component units / water-soluble polymer) is, for example, less than 10 mol %, less than 9 mol %, less than 7 mol %, less than 5 mol %, less than 4 mol %, less than 3 mol %, less than 2 mol %, less than 1 mol %, or 0 mol %. In one embodiment, the content is preferably less than 10 mol %, more preferably less than 5 mol %, further preferably less than 1 mol %, and particularly preferably 0 mol %.

[0087] <Production method (water-soluble polymer)> Examples of the production method (water-soluble polymer) include radical polymerization, etc. In one embodiment, the polymerization temperature is preferably 50° C. to 100° C. In one embodiment, the polymerization time is preferably 1 hour to 10 hours.

[0088] Examples of the radical polymerization initiator include an azo initiator, a persulfate, and a redox polymerization initiator.

[0089] Examples of the azo initiator include 2,2′-azobis(2-amidinopropane) dihydrochloride and the like.

[0090] Examples of the persulfate include potassium persulfate and ammonium persulfate.

[0091] Examples of the redox polymerization initiator include a system in which the above-mentioned persulfate and a reducing agent are combined.

[0092] Examples of the reducing agent include sodium bisulfite and the like.

[0093] The amount used in mass % (radical polymerization initiator / monomer group) is preferably 0.05 mass % to 5.0 mass %, more preferably 0.05 mass % to 3.0 mass %.

[0094] In one embodiment, examples of the polymerization method (water-soluble polymer) include only simultaneous polymerization, only dropwise polymerization, and a combination of simultaneous polymerization and dropwise polymerization.

[0095] "Dropwise polymerization" refers to a polymerization method in which a monomer solution is dropped into a reaction system.

[0096] "Simultaneous polymerization" refers to a polymerization method in which the monomer solution is added all at once.

[0097] Examples of the method using only dropwise polymerization include (1) to (3) etc. Dropwise addition may be continuous or stopped halfway and then restarted after polymerization for a certain period of time. (1) A method in which a monomer mixture solution containing all monomer components is added dropwise to a reaction system. (2) A method in which two or more monomer mixed solutions are prepared separately and then added dropwise to the reaction system simultaneously. (3) A method in which two or more monomer mixed solutions are prepared separately and then added dropwise to the reaction system in sequence.

[0098] Examples of the method of combining simultaneous polymerization and dropping polymerization include (4) to (7). (4) A method in which each monomer mixed solution is polymerized simultaneously and then each polymer is mixed. (5) A method in which, after the simultaneous polymerization of one or more monomer mixed solutions is completed, the remaining monomer mixed solution is added dropwise. (6) A method in which during the simultaneous polymerization of one or more monomer mixed solutions, the remaining monomer mixed solution is added dropwise to carry out polymerization. (7) A method in which one or more monomer mixtures are dropwise polymerized, and the remaining monomer mixtures are added all at once and then polymerized simultaneously.

[0099] <Physical properties (water-soluble polymers), etc.> The weight average molecular weight (water-soluble polymer: Mw) includes, for example, 6 million, 5.5 million, 5 million, 4.5 million, 4 million, 3.5 million, 3 million, 2.5 million, 2 million, 1.5 million, 1 million, 950,000, 900,000, 850,000, 800,000, 750,000, 700,000, 650,000, 600,000, 550,000, 500,000, 450,000, 400,000, 350,000, 300,000, 250,000, 200,000, 150,000, 100,000, etc. In one embodiment, the weight average molecular weight (Mw) is preferably 100,000 to 6 million, and more preferably 350,000 to 6 million.

[0100] The number average molecular weight (water-soluble polymer: Mn) includes, for example, 6 million, 5.5 million, 5 million, 4.5 million, 4 million, 3.5 million, 3 million, 2.5 million, 2 million, 1.5 million, 1 million, 950,000, 900,000, 850,000, 800,000, 750,000, 700,000, 650,000, 600,000, 550,000, 500,000, 450,000, 400,000, 300,000, 200,000, 100,000, 50,000, 10,000, etc. In one embodiment, the number average molecular weight (Mn) is preferably 10,000 or more.

[0101] Examples of the molecular weight distribution (water-soluble polymer: Mw / Mn) include 15, 14, 13, 11, 10, 9, 7.5, 5, 4, 3, 2.9, 2.5, 2, 1.5, and 1.1. In one embodiment, the molecular weight distribution (Mw / Mn) is preferably 1.1-15.

[0102] Examples of measurement conditions (weight average molecular weight, number average molecular weight, average radius of inertia) include the following conditions. ·Measurement instrument: GPC (model: HLC-8420) manufactured by Tosoh Corporation Column: TSKgel guardcolumn PWXL 1 piece, TSKgel GMPWXL 1 piece (manufactured by Tosoh Corporation) · Eluent: Phosphate buffer (0.284 mol / L disodium hydrogen phosphate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) + 0.016 mol / L sodium dihydrogen phosphate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) aqueous solution, pH 8.0) Column temperature: 40℃ RI detector: Shodex RI-101 manufactured by Showa Denko (Showa Denko) MALS detector: DAWN HELEOS-II manufactured by WYATT Flow rate: 0.8ml / min ·Measurement concentration: 0.10 mass % (water-soluble polymer concentration) ·Measurement method: Measure after filtering. Filter: Cellulose acetate cartridge filter (manufactured by Tosoh Corporation, Microdiesk W-13-2, pore size 0.2 μm)

[0103] The average inertia radius (water-soluble polymer) includes, for example, 250 nm, 240 nm, 230 nm, 220 nm, 210 nm, 200 nm, 190 nm, 180 nm, 170 nm, 160 nm, 150 nm, 140 nm, 130 nm, 120 nm, 110 nm, 100 nm, 90 nm, 80nm, 70nm, 60nm, 50nm, 40nm, 30nm, 20nm, etc. In one embodiment, the average inertia radius is preferably 20nm to 250nm, more preferably 20nm to 160nm, and even more preferably 30nm to 150nm.

[0104] The value calculated by Formula 1 represents the degree of branching of the water-soluble polymer. The larger the value calculated by Formula 1, the more branching there is. Formula 1: (Mw / Mn)×(Mw / Rw)×10 -4 (Wherein, Mw is the weight average molecular weight, Mn is the number average molecular weight, and Rw is the average inertia radius (nm).)

[0105] Examples of the value calculated by Formula 1 include 8.0, 7.5, 7.0, 6.5, 6.0, 5.5, 5.0, 4.5, 4.0, 3.5, 3.0, 2.9, and 2.8. In one embodiment, the value calculated by Formula 1 is preferably 2.8 or more, more preferably 2.8 to 8.0, further preferably 2.8 to 6.5, and particularly preferably 2.8 to 5.0.

[0106] (Common logarithm of viscosity-non-volatile content function) The "linear function" refers to a function represented by the following formula. y=ax+b (x is the horizontal axis. y is the vertical axis. a is the slope. b is the intercept.)

[0107] The least squares method can be implemented using spreadsheet software.

[0108] Examples of spreadsheet software include Microsoft Excel and the like.

[0109] In one embodiment, the least squares method may be implemented using Microsoft Excel's LINEST function.

[0110] The common logarithm is log 10 A. (A indicates a positive number.)

[0111] The slope of the linear function obtained by the least square method for the following vertical axis and horizontal axis represents the degree of branching of the water-soluble polymer. The smaller the above slope, the more branching there is. Vertical axis: Common logarithm of the viscosity (mPa·s) of the aqueous solution of the water-soluble polymer Horizontal axis: non-volatile content of aqueous solution of the water-soluble polymer (%)

[0112] Examples of the slope include 0.25, 0.24, 0.23, 0.22, 0.21, 0.20, 0.19, 0.18, 0.17, 0.16, 0.15, 0.14, 0.13, 0.12, 0. In one embodiment, the slope is preferably 0.10 to 0.25, more preferably 0.10 to 0.21.

[0113] Examples of the intercept include 1.9, 1.8, 1.7, 1.6, 1.5, 1.4, 1.3, and 1.2. In one embodiment, the intercept is preferably 1.2 to 1.9, and more preferably 1.3 to 1.9.

[0114] Examples of the B-type viscosity (electrical storage device binder aqueous solution) include 100,000 mPa·s, 90,000 mPa·s, 80,000 mPa·s, 70,000 mPa·s, 60,000 mPa·s, 50,000 mPa·s, 40,000 mPa·s, 30,000 mPa·s, 20,000 mPa·s, 10,000 mPa·s, 9000 mPa·s, 8000 mPa·s, 7000 mPa·s, 6000 mPa·s, 5000 mPa·s, 4000 mPa·s, 3000 mPa·s, 2000 mPa·s, and 1000 mPa·s. In one embodiment, the B-type viscosity is preferably 1000 mPa·s to 1000,000 mPa·s.

[0115] The measurement conditions (B-type viscosity) include, for example, the following conditions. Solid content: 15% by mass Measurement temperature: 25℃ B-type viscometer: manufactured by Toki Sangyo Co., Ltd. (Toki Sangyo Co., Ltd.), product name "B-type viscometer TVB-10" Viscosity 100~10000mPa·s: No.3 rotor, speed 12rpm Viscosity over 10000-20000 mPa·s: No.3 rotor, speed 6 rpm Viscosity over 20000100000 mPa·s: No.4 rotor, speed 6 rpm

[0116] The glass transition temperature (water-soluble polymer) is, for example, 160°C, 155°C, 150°C, 145°C, 140°C, 135°C, 130°C, 125°C, 120°C, 115°C, 110°C, 105°C, 100°C, 95°C, 90°C, 85°C, 80°C, 75°C, 70°C, 65°C, 60°C, 55°C, 50°C, 45°C, 40°C, 35°C, 30°C, 25°C, 20°C, 15°C, 10°C, 5°C, 0°C, etc. In one embodiment, the glass transition temperature is preferably 0°C or higher, more preferably 30°C or higher.

[0117] Based on the glass transition temperature (homopolymer) and the mass fraction (monomer), the glass transition temperature (water-soluble polymer) can be calculated using the Fox equation. 1 / Tg=(W1 / Tg1)+(W2 / Tg2)+(W3 / Tg3)+···+(W n / Tg n )[Fox formula, Tg represents the glass transition temperature of the polymer to be determined (K), W1~W n Indicates the mass fraction of each monomer, Tg1~Tg n represents the glass transition temperature of each monomer (homopolymer) (K)]

[0118] The glass transition temperature can be measured by DSC (differential scanning calorimeter), DTA (differential thermal analyzer), TMA (thermomechanical analyzer) or the like. Examples of measurement conditions (glass transition temperature) include the following conditions. Temperature range: -100℃~300℃ Heating rate: 10℃ / min

[0119] The glass transition temperature (homopolymer) may also be a value described in the literature. Examples of the literature include "Basic Chemical Handy Manual II, edited by the Chemical Society of Japan (revised 5th edition)", p325. Examples of the glass transition temperature (homopolymer) include the following temperatures. Examples of the glass transition temperature (homopolymer) include the following temperatures. Acrylamide: 165℃ Acrylic acid: 106°C Hydroxyethyl acrylate: -15°C Acrylonitrile: 105℃

[0120] The mass % content (water-soluble polymer / electrical storage device binder aqueous solution) is, for example, 25 mass %, 20 mass %, 19 mass %, 15 mass %, 14 mass %, 12 mass %, 10 mass %, 9 mass %, 7 mass %, 6 mass%, 5 mass%, 4 mass%, 3 mass%, 2 mass%, 1 mass%, etc. In one embodiment, the content is preferably 1 mass% to 25 mass%.

[0121] <Water> Examples of water include ultrapure water, pure water, distilled water, ion-exchanged water, and tap water.

[0122] Examples of the mass % content (water / electrical storage device binder aqueous solution) include 99.9 mass %, 99 mass %, 95 mass %, 90 mass %, 85 mass %, 80 mass %, 75 mass %, etc. In one embodiment, the content is preferably 75 mass % to 99.9 mass %.

[0123] Examples of the mass ratio (water-soluble polymer / water) include 0.33, 0.30, 0.25, 0.24, 0.22, 0.20, 0.18, 0.15, 0.12, 0.10, 0.09, 0.07, and 0.05. In one embodiment, the mass ratio is preferably 0.05 to 0.33.

[0124] <Other adhesives> In one embodiment, the electrical storage device binder aqueous solution may optionally contain a binder other than the water-soluble polymer (other binder). Other binders may be used alone or in combination of two or more.

[0125] Examples of other binders include diene copolymers, fluorine copolymers, amide-imide copolymers, and copolymers other than those listed above.

[0126] Examples of the diene copolymer include styrene-butadiene copolymers, polybutadiene polymers, acrylonitrile-butadiene copolymers, methyl methacrylate-butadiene copolymers, and carboxyl-modified styrene-butadiene copolymers.

[0127] Examples of the fluorine-based copolymer include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), and ethylene-tetrafluoroethylene copolymer (ETFE).

[0128] Examples of the amide-imide copolymer include polyamide (PA), polyimide (PI), polyamideimide (PAI), and aromatic polyamide.

[0129] Examples of copolymers other than those mentioned above include polyurethane polymers, poly(meth)acrylate polymers, vinyl chloride polymers, vinyl acetate polymers, vinyl acetate-ethylene copolymers, polyethylene, polypropylene, polyethylene terephthalate, polystyrene polymers, alginic acid and / or its salts.

[0130] The content (other binders / water-soluble polymers) in parts by mass includes, for example, 100 parts by mass, 95 parts by mass, 90 parts by mass, 85 parts by mass, 80 parts by mass, 75 parts by mass, 70 parts by mass, 65 parts by mass, 60 parts by mass, 55 parts by mass, 50 parts by mass, 45 parts by mass, 40 parts by mass, 35 parts by mass, 30 parts by mass, 25 parts by mass, 20 parts by mass, 19 parts by mass, 17 parts by mass, 15 parts by mass, 13 parts by mass, 10 parts by mass, 9 parts by mass, 7 parts by mass, 5 parts by mass, 4 parts by mass, 2 parts by mass, 1 part by mass, 0 parts by mass, etc. In one embodiment, the content preferably includes 0 parts by mass to 100 parts by mass.

[0131] <Dispersion (emulsion)> In one embodiment, the aqueous solution of the electrical storage device binder may optionally contain a dispersion (emulsion). The dispersions (emulsions) may be used alone or in combination of two or more.

[0132] Examples of the dispersion (emulsion) include styrene-butadiene copolymer latex, polystyrene polymer latex, polybutadiene polymer latex, acrylonitrile-butadiene copolymer latex, polyurethane polymer latex, polymethyl methacrylate polymer latex, methyl methacrylate-butadiene copolymer latex, polyacrylate polymer latex, vinyl chloride polymer latex, vinyl acetate polymer latex, vinyl acetate-ethylene copolymer latex, polyethylene latex, carboxyl-modified styrene-butadiene copolymer resin latex, acrylic resin emulsion, polyethylene, polypropylene, polyethylene terephthalate, polyamide (PA), polyimide (PI), polyamideimide (PAI), aromatic polyamide, alginic acid and its salts, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), ethylene-tetrafluoroethylene copolymer (ETFE), and the like.

[0133] The mass content (dispersion (emulsion) / water-soluble polymer) is exemplified by 100 mass parts, 95 mass parts, 90 mass parts, 85 mass parts, 80 mass parts, 75 mass parts, 70 mass parts, 65 mass parts, 60 mass parts, 55 mass parts, 50 mass parts, 45 mass parts, 40 mass parts, 35 mass parts, 30 mass parts, 25 mass parts, 20 mass parts, 19 mass parts, 17 mass parts, 15 mass parts, 13 mass parts, 10 mass parts, 9 mass parts, 7 mass parts, 5 mass parts, 4 mass parts, 2 mass parts, 1 mass part, 0 mass parts, etc. In one embodiment, the content is preferably 0 mass parts to 100 mass parts.

[0134] <Thickener> In one embodiment, the aqueous solution of the electrical storage device binder may optionally contain a thickener. The thickener may be used alone or in combination of two or more.

[0135] Examples of the thickener include cellulose polymers and / or salts thereof, polyvinyl alcohols, (modified) poly(meth)acrylic acid and / or salts thereof, polyethylene glycol, polyethylene oxide, polyvinyl pyrrolidone, oxidized starch, starch phosphate, casein, modified starch, hydrogenated acrylonitrile-butadiene copolymer, and the like.

[0136] Examples of the cellulose-based polymer and / or its salt include carboxymethyl cellulose, methyl cellulose, and hydroxypropyl cellulose.

[0137] Examples of the polyvinyl alcohols include copolymers of maleic acid (anhydride) and / or fumaric acid and vinyl alcohol.

[0138] The content (thickener / water-soluble polymer) in parts by mass is exemplified by 100 parts by mass, 95 parts by mass, 90 parts by mass, 85 parts by mass, 80 parts by mass, 75 parts by mass, 70 parts by mass, 65 parts by mass, 60 parts by mass, 55 parts by mass, 50 parts by mass, 45 parts by mass, 40 parts by mass, 35 parts by mass, 30 parts by mass, 25 parts by mass, 20 parts by mass, 19 parts by mass, 17 parts by mass, 15 parts by mass, 13 parts by mass, 10 parts by mass, 9 parts by mass, 7 parts by mass, 5 parts by mass, 4 parts by mass, 2 parts by mass, 1 part by mass, 0 parts by mass, etc. In one embodiment, the content is preferably 0 to 100 parts by mass.

[0139] <Additives> The aqueous solution of the electrical storage device binder may optionally contain an agent other than a water-soluble polymer, water, other binders, dispersions (emulsions), or thickeners as an additive. The additive may be used alone or in combination of two or more.

[0140] Examples of the additives include a dispersant, a leveling agent, and an antioxidant.

[0141] Examples of the dispersant include anionic dispersants, cationic dispersants, nonionic dispersants, and polymer dispersants.

[0142] Examples of the leveling agent include surfactants and the like.

[0143] Examples of the surfactant include alkyl surfactants, silicone surfactants, fluorine surfactants, and metal surfactants.

[0144] Examples of the antioxidant include phenol compounds, hydroquinone compounds, organic phosphine compounds, sulfur compounds, phenylenediamine compounds, and polymer-type phenol compounds.

[0145] The "polymer type phenol compound" refers to a polymer having a phenol structure. The weight average molecular weight (polymer type phenol compound) is preferably 200 to 1,000, more preferably 600 to 700.

[0146] Examples of the content (additive / water-soluble polymer) include less than 5 parts by mass, less than 4 parts by mass, less than 2 parts by mass, less than 1 part by mass, less than 0.9 parts by mass, less than 0.5 parts by mass, less than 0.4 parts by mass, less than 0.2 parts by mass, less than 0.1 parts by mass, less than 0.09 parts by mass, less than 0.05 parts by mass, less than 0.04 parts by mass, less than 0.02 parts by mass, less than 0.01 parts by mass, and 0 parts by mass.

[0147] Examples of the mass % content (additive / electrical storage device binder aqueous solution) include less than 5 mass %, less than 4 mass %, less than 2 mass %, less than 1 mass %, less than 0.9 mass %, less than 0.5 mass %, less than 0.4 mass %, less than 0.2 mass %, less than 0.1 mass %, less than 0.09 mass %, less than 0.05 mass %, less than 0.04 mass %, less than 0.02 mass %, less than 0.01 mass %, and 0 mass %.

[0148] Examples of pH (electrical storage device binder aqueous solution) include 9, 8.9, 8.5, 8, 7.9, 7.5, 7, 6.9, 6.5, 6, 5.9, 5.6, 5.5, 5.4, 5.2, 5.1, and 5. In one embodiment, the pH is preferably 5-9, more preferably 5-7.

[0149] Examples of measurement conditions (pH) include the following conditions. Measuring instrument: Product name: pH meter D-52 manufactured by Horiba, Ltd. Measuring temperature: 25°C

[0150] Applications (aqueous solution of binder for power storage devices) include, for example, aqueous solution of binder for power storage device electrodes, aqueous solution of binder for battery electrodes, aqueous solution of binder for non-aqueous secondary battery electrodes, aqueous solution of binder for lithium ion battery electrodes, aqueous solution of binder for sodium ion battery electrodes, aqueous solution of binder for negative electrode of power storage device, aqueous solution of binder for negative electrode of battery, aqueous solution of binder for negative electrode of non-aqueous secondary battery electrodes, aqueous solution of binder for negative electrode of lithium ion battery electrodes, aqueous solution of binder for negative electrode of sodium ion battery, aqueous solution of binder for positive electrode of power storage device, aqueous solution of binder for positive electrode of battery, aqueous solution of binder for positive electrode of non-aqueous secondary battery electrodes, aqueous solution of binder for positive electrode of lithium ion battery electrodes, aqueous solution of binder for positive electrode of sodium ion battery, aqueous solution of binder for separator of power storage device, aqueous solution of binder for separator of battery, aqueous solution of binder for separator of non-aqueous secondary battery electrodes, aqueous solution of binder for separator of lithium ion battery electrodes, aqueous solution of binder for separator of sodium ion battery electrodes, etc.

[0151] [Electricity storage device slurry: slurry] The present invention relates to a slurry for an electric storage device. The electrical storage device slurry comprises a water-soluble polymer and water, The water-soluble polymer comprises 10 mol% to 99.85 mol% of (meth)acrylamide units, 0.001 mol% to 20 mol% of alkyl (meth)acrylamide units and / or multifunctional monomer units, and 0.001 mol% to 2.0 mol% of unsaturated hydrocarbon sulfonic acid units.

[0152] "Slurry" refers to a suspension of liquid and solid particles.

[0153] Examples of the water-soluble polymer, water, other binders, dispersions (emulsions), and thickeners include those mentioned above.

[0154] The mass % content (water-soluble polymer / slurry) includes, for example, 10 mass %, 9 mass %, 8 mass %, 7 mass %, 6 mass %, 5 mass %, 4 mass %, 3 mass %, 2 mass %, 1 mass %, 0.9 mass %, 0.7 mass %, 0.5 mass %, 0.3 mass %, 0.1 mass %, etc. In one embodiment, the content is preferably 0.1 mass % to 10 mass %.

[0155] Examples of the mass % content (water / slurry) include 80 mass %, 75 mass %, 70 mass %, 65 mass %, 60 mass %, 55 mass %, 50 mass %, 45 mass %, 40 mass %, 35 mass %, 30 mass %, etc. In one embodiment, the content is preferably 30 mass % to 80 mass %.

[0156] Examples of the content (other binders), the content (dispersion (emulsion)), and the content (thickener) include the above-mentioned contents.

[0157] <Electrode active material> In one embodiment, the electrical storage device slurry contains an electrode active material. Examples of the electrode active material include a negative electrode active material and a positive electrode active material. The electrode active material may be used alone or in combination of two or more.

[0158] (Negative electrode active material) Examples of the negative electrode active material include carbon materials, materials that can be alloyed with lithium, silicon materials, and oxides containing lithium atoms.

[0159] Examples of the carbon material include graphite, low-crystalline carbon, carbon black, fullerene, carbon nanotube, carbon nanofiber, carbon nanohorn, carbon fibril, mesocarbon microbeads (MCMB), pitch-based carbon fibers, and activated carbon.

[0160] Examples of graphite include natural graphite and artificial graphite.

[0161] Examples of low-crystalline carbon include soft carbon and hard carbon.

[0162] Examples of carbon black include Ketjen black, acetylene black, channel black, lamp black, oil furnace black, thermal black, and the like.

[0163] Examples of the material that alloys with lithium include lead compounds, tin compounds, arsenic compounds, antimony compounds, and aluminum compounds.

[0164] Silicon materials include silicon, silicon oxide, silicon alloy, SiC, SiO x C y(0<x≤3, 0<y≤5), Si3N4, Si2N2O, SiO z (0<z≤2) etc.

[0165] Silicon oxide preferably has a composition formula SiO z Silicon oxide represented by (0<z≤2, preferably 0.1≤z≤1).

[0166] Examples of silicon alloys include silicon-titanium alloys, silicon-zirconium alloys, silicon-nickel alloys, silicon-copper alloys, silicon-iron alloys, silicon-molybdenum alloys, etc. In one embodiment, the silicon alloy preferably includes silicon-nickel alloys and silicon-titanium alloys, and more preferably includes silicon-titanium alloys.

[0167] The mol% content (silicon atoms / total metal elements) is preferably 10 mol% or more, more preferably 20 mol% to 70 mol%.

[0168] Examples of the shape of the silicon material include single crystal, polycrystalline, and amorphous.

[0169] When a silicon material is used as the electrode active material, an electrode active material other than the silicon material may be used in combination.

[0170] Examples of electrode active materials other than silicon materials include carbon materials, conductive polymers, and composite metal oxides.

[0171] Examples of the conductive polymer include polyacene and the like.

[0172] The composite metal oxide is represented by, for example, the following general formula. A α B β O γ (A represents an alkali metal or a transition metal. B represents at least one transition metal selected from cobalt, nickel, aluminum, tin, manganese and the like. O represents an oxygen atom. α, β and γ are independently 0.05<α<1.10, 0.85<β<4.00, and 1.5<γ<5.00.)

[0173] Carbon materials have a small volume change associated with the absorption and release of lithium. Therefore, when a silicon material is used as an electrode active material, it is preferably used in combination with a carbon material.

[0174] In one embodiment, the silicon material preferably includes silicon covered with a carbon layer and silicon oxide covered with a carbon layer.

[0175] Examples of the lithium atom-containing oxide include lithium-transition metal composite oxides, lithium-transition metal phosphate compounds, and lithium-transition metal sulfate compounds.

[0176] Examples of the lithium-transition metal composite oxide include lithium-manganese composite oxide, lithium-nickel composite oxide, lithium-cobalt composite oxide, lithium-iron composite oxide, lithium-titanium composite oxide, lithium-nickel-manganese composite oxide, and lithium-nickel-cobalt composite oxide.

[0177] In one embodiment, mass % content (carbon material and / or material / negative electrode active material alloyed with lithium) for example, 100 mass %, 95 mass %, 90 mass %, 85 mass %, 80 mass %, 75 mass %, 70 mass %, 65 mass %, 60 mass %, 55 mass %, 50 mass %, 45 mass %, 40 mass %, 35 mass %, 30 mass %, 25 mass %, 20 mass %, 15 mass %, 10 mass %, 5 mass %, 0 mass %, etc. In one embodiment, the content preferably cites more than 50 mass %, more preferably cites more than 80 mass %, further preferably cites more than 90 mass %, and particularly preferably cites 100 mass %.

[0178] In one embodiment, the mass % content (silicon covered by the carbon layer and / or silicon oxide covered by the carbon layer / negative electrode active material) is, for example, 100 mass %, 90 mass % or more, 75 mass % or more, 50 mass % or more, 25 mass % or more, 10 mass % or more, 5 mass % or more, 2 mass % or more, 1 mass % or more, 0 mass %, etc.

[0179] In one embodiment, the mass % content (silicon material / negative electrode active material) is, for example, 100 mass %, 95 mass %, 90 mass %, 85 mass %, 80 mass %, 75 mass %, 70 mass %, 65 mass %, 60 mass %, 55 mass %, 50 mass %, 45 mass %, 40 mass %, 35 mass %, 30 mass %, 25 mass %, 20 mass %, 15 mass %, 10 mass %, 5 mass %, 0 mass %, etc.

[0180] (Positive electrode active material) Examples of the positive electrode active material include positive electrode inorganic active materials and positive electrode organic active materials.

[0181] Examples of the positive electrode inorganic active material include transition metal oxides, lithium-transition metal composite oxides, transition metal sulfides, activated carbon, and the like.

[0182] The inorganic active material may be partially substituted with an element. By allowing a carbon source material to be present during reduction firing, the inorganic active material can be used as an electrode active material covered with a carbon material.

[0183] Examples of the positive electrode organic active material include conductive polymers.

[0184] Examples of the conductive polymer include polyacetylene and poly-p-phenylene.

[0185] (Physical properties, etc. (electrode active material)) Examples of the shape (electrode active material) include fine particle shape and thin film shape.

[0186] The average particle size (electrode active material) is preferably 0.1 to 50 μm, more preferably 0.1 to 45 μm, further preferably 1 to 10 μm, and particularly preferably 5 μm.

[0187] "Particle size" refers to the maximum distance between any two points on the contour line of a particle. "Average particle size" refers to a value calculated as the average value of the particle sizes of particles observed in several to dozens of fields of view using an observation method such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM).

[0188] The content (water-soluble polymer / electrode active material) in parts by mass includes 15 parts by mass, 14 parts by mass, 13 parts by mass, 12 parts by mass, 11 parts by mass, 10 parts by mass, 9 parts by mass, 8 parts by mass, 7 parts by mass, 6 parts by mass, 5 parts by mass, 4 parts by mass, 3 parts by mass, 2 parts by mass, 1.5 parts by mass, 1 part by mass, 0.5 parts by mass, etc. In one embodiment, the content is preferably 0.5 parts by mass to 15 parts by mass.

[0189] (Conductive additive) In one embodiment, the slurry may optionally include a conductive additive. The conductive additive may be used alone or in combination of two or more.

[0190] Examples of the conductive additive include fibrous carbon, carbon black, and metal fine powder.

[0191] Examples of fibrous carbon include vapor grown carbon fibers (VGCF), carbon nanotubes (CNTs), and carbon nanofibers (CNFs).

[0192] Examples of carbon black include graphite particles, acetylene black, Ketjen black, furnace black, and the like.

[0193] Examples of the metal fine powder include copper fine powder, nickel fine powder, aluminum fine powder, silicon fine powder, and alloy fine powder.

[0194] In one embodiment, the average particle size (metal fine powder) is preferably 10 μm.

[0195] The content (conductive aid / electrode active material) is preferably 0 to 10 parts by mass, more preferably 0 to 6 parts by mass.

[0196] <Non-conductive particles> In one embodiment, the electrical storage device slurry contains non-conductive particles. The non-conductive particles may be used alone or in combination of two or more.

[0197] Examples of the non-conductive particles include oxide particles, hydroxide particles, nitride particles, covalent crystal particles, poorly soluble ion crystal particles, clay fine particles, aluminum particles, barium particles, and calcium particles.

[0198] Examples of oxide particles include aluminum oxide (alumina), aluminum oxide hydrate (boehmite (AlOOH), gibbsite (Al(OH)3), iron oxide, silicon oxide, magnesium oxide (magnesia), calcium oxide, titanium oxide (titanium oxide), BaTiO3, ZrO, and aluminum oxide-silicon dioxide composite oxides.

[0199] Examples of the hydroxide particles include calcium hydroxide and magnesium hydroxide.

[0200] Examples of nitride particles include aluminum nitride, silicon nitride, and boron nitride.

[0201] Examples of covalent crystals include silicon and diamond.

[0202] Examples of the poorly soluble ion crystals include barium sulfate, calcium fluoride, and barium fluoride.

[0203] Examples of the clay fine particles include clay fine particles such as silica, talc, and montmorillonite.

[0204] Examples of aluminum particles include alumina (alumina), alumina hydrate (boehmite (AlOOH), gibbsite (Al(OH) 3 ), and aluminum nitride.

[0205] Examples of the barium particles include barium sulfate and barium fluoride.

[0206] Examples of the calcium particles include calcium hydroxide, magnesium hydroxide, and calcium fluoride.

[0207] In one embodiment, preferred non-conductive particles include boehmite, aluminum oxide, magnesium oxide, and barium sulfate.

[0208] Examples of the average particle size (non-conductive particles) include 30 μm, 25 μm, 20 μm, 15 μm, 10 μm, 5 μm, 1 μm, 0.5 μm, 0.1 μm, 0.05 μm, and 0.01 μm. In one embodiment, the average particle size is preferably 0.01 μm to 30 μm.

[0209] The mass % content (non-conductive particles / paste) includes, for example, 99.9 mass %, 95 mass %, 90 mass %, 80 mass %, 70 mass %, 60 mass %, 50 mass %, 40 mass %, 30 mass %, 20 mass %, 10 mass %, 5 mass %, 1 mass %, 0.5 mass %, 0.2 mass %, 0.1 mass %, etc. In one embodiment, the content is preferably 0.1 mass % to 99.9 mass %.

[0210] The content (water-soluble polymer / non-conductive particles) in parts by mass includes, for example, 15 parts by mass, 14 parts by mass, 13 parts by mass, 12 parts by mass, 11 parts by mass, 10 parts by mass, 9 parts by mass, 8 parts by mass, 7 parts by mass, 6 parts by mass, 5 parts by mass, 4 parts by mass, 3 parts by mass, 2 parts by mass, 1.5 parts by mass, 1 part by mass, etc. In one embodiment, the content is preferably 1 to 15 parts by mass, more preferably 1.5 to 14 parts by mass, and even more preferably 2 to 12 parts by mass.

[0211] <Slurry Viscosity Adjusting Solvent> The slurry viscosity adjusting solvent may be used alone or in combination of two or more.

[0212] Examples of the slurry viscosity adjusting solvent include amide solvents, hydrocarbon solvents, alcohol solvents, ketone solvents, ether solvents, ester solvents, amine solvents, lactone solvents, sulfoxide / sulfone solvents, and water.

[0213] Examples of the amide solvent include N-methylpyrrolidone, dimethylformamide, and N,N-dimethylacetamide.

[0214] Examples of the hydrocarbon solvent include toluene, xylene, n-dodecane, and tetralin.

[0215] Examples of the alcohol solvent include methanol, ethanol, 2-propanol, isopropanol, 2-ethyl-1-hexanol, 1-nonanol, and lauryl alcohol.

[0216] Examples of the ketone solvent include acetone, methyl ethyl ketone, cyclohexanone, phorone, acetophenone, and isophorone.

[0217] Examples of the ether solvent include dioxane and tetrahydrofuran (THF).

[0218] Examples of the ester solvent include benzyl acetate, isoamyl butyrate, methyl lactate, ethyl lactate, and butyl lactate.

[0219] Examples of the amine solvent include o-toluidine, m-toluidine, and p-toluidine.

[0220] Examples of the lactone solvent include γ-butyrolactone and δ-butyrolactone.

[0221] Examples of the sulfoxide / sulfone solvent include dimethyl sulfoxide and sulfolane.

[0222] In one embodiment, the slurry viscosity adjusting solvent is preferably N-methylpyrrolidone.

[0223] Examples of the mass % content (slurry viscosity adjusting solvent / slurry) include 10 mass %, 9 mass %, 8 mass %, 7 mass %, 6 mass %, 5 mass %, 4 mass %, 3 mass %, 2 mass %, 1 mass %, 0 mass %, etc. In one embodiment, the content is preferably 0 to 10 mass %.

[0224] <Additives> The slurry may optionally contain an agent other than a water-soluble polymer, water, other binders, dispersions (emulsions), thickeners, electrode active materials, non-conductive particles, and slurry viscosity adjusting solvents as additives. Examples of the additives include the above-mentioned agents.

[0225] Examples of the mass % content (additive / slurry) include 0 mass % to 5 mass %, less than 1 mass %, less than 0.1 mass %, less than 0.01 mass %, and 0 mass %.

[0226] The content by mass (additive / water-soluble polymer), the content by mass (additive / water), the content by mass (additive / other binders), the content by mass (additive / dispersion (emulsion)), the content by mass (additive / thickener), the content by mass (additive / electrode active material), the content by mass (additive / non-conductive particles), the content by mass (additive / slurry viscosity adjusting solvent) include, for example, 0 to 5 parts by mass, less than 1 part by mass, less than 0.1 part by mass, less than 0.01 part by mass, 0 part by mass, etc.

[0227] The slurry can be produced by mixing a water-soluble polymer, water, and an electrode active material or non-conductive particles, and, if necessary, other binders, dispersions (emulsions), thickeners, slurry viscosity adjusting solvents, and additives.

[0228] Examples of the mixing means (slurry) include a ball mill, a sand mill, a pigment disperser, a pounder, an ultrasonic disperser, a homogenizer, a planetary mixer, and a Hobart mixer.

[0229] Examples of the use (electrical storage device slurry) include electrical storage device electrode slurry, battery electrode slurry, non-aqueous secondary battery electrode slurry, lithium ion battery electrode slurry, sodium ion battery electrode slurry, electrical storage device negative electrode slurry, battery negative electrode slurry, non-aqueous secondary battery negative electrode slurry, lithium ion battery negative electrode slurry, sodium ion battery negative electrode slurry, electrical storage device positive electrode slurry, battery positive electrode slurry, non-aqueous secondary battery positive electrode slurry, lithium ion battery positive electrode slurry, sodium ion battery positive electrode slurry, electrical storage device diaphragm slurry, battery diaphragm slurry, non-aqueous secondary battery diaphragm slurry, lithium ion battery diaphragm slurry, sodium ion battery diaphragm slurry, etc.

[0230] [Electrodes for power storage devices: Electrodes] The present disclosure relates to an electric storage device electrode having a dried product of the electric storage device slurry on a current collector.

[0231] The electric storage device electrode is obtained by applying the electric storage device slurry onto a current collector and drying the slurry.

[0232] Examples of the current collector include metal materials and carbon materials.

[0233] Examples of the metal material include copper, iron, aluminum, nickel, stainless steel, and nickel-plated steel.

[0234] Examples of the form of the metal material include metal foil, metal cylinder, metal coil, and metal plate.

[0235] Examples of the carbon material include carbon cloth and carbon paper.

[0236] Examples of the form (carbon material) include a carbon plate, a carbon film, and a carbon cylinder.

[0237] Examples of coating means include a comma coater, a gravure coater, a micro gravure coater, a die coater, and a rod coater.

[0238] The drying temperature is preferably 60°C to 200°C, more preferably 70°C to 195°C.

[0239] Examples of the dry atmosphere include dry air and an inert atmosphere.

[0240] The thickness (electrode (cured product)) is preferably 5 μm to 300 μm, more preferably 10 μm to 250 μm.

[0241] Examples of uses (electrical storage device electrodes) include electric storage device positive electrodes, electric storage device negative electrodes, battery electrodes, battery positive electrodes, battery negative electrodes, non-aqueous secondary battery electrodes, non-aqueous secondary battery positive electrodes, non-aqueous secondary battery negative electrodes, lithium ion battery electrodes, lithium ion battery positive electrodes, lithium ion battery negative electrodes, sodium ion battery electrodes, sodium ion battery positive electrodes, sodium ion battery negative electrodes, etc.

[0242] [Electricity storage device diaphragm: diaphragm] The present disclosure relates to an electric storage device separator having a dried product of the electric storage device slurry on a substrate.

[0243] The electrical storage device separator can be produced by applying the electrical storage device separator slurry on one side or both sides of a substrate and drying the slurry.

[0244] Examples of the substrate include porous polyolefin resin substrates and plastic nonwoven fabrics.

[0245] (Porous polyolefin resin substrate) The “porous polyolefin resin substrate” refers to a microporous film containing 30% by mass or more of a resin such as polyolefin or a mixture or copolymer thereof.

[0246] The polyolefin resin may be used alone or in combination of two or more. Examples of the polyolefin resin include homopolymers and copolymers of ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene.

[0247] Examples of the stereostructure (polyolefin) include isotactic, syndiotactic and atactic.

[0248] In one embodiment, the polyolefin resin preferably includes high-density polyethylene, and more preferably includes high-density polyethylene and polypropylene.

[0249] In one embodiment, the mass % content (polyolefin resin / substrate) is preferably 30 mass % to 100 mass %, more preferably 40 mass % to 100 mass %, and further preferably 50 mass % to 100 mass %.

[0250] The porous polyolefin resin substrate may optionally contain fillers and fiber compounds. The strength, hardness and thermal shrinkage of the porous polyolefin resin substrate may be controlled by fillers and fiber compounds.

[0251] The porous polyolefin resin substrate may be surface-treated as necessary.

[0252] Examples of the surface treatment include coating treatment, electromagnetic wire treatment, and plasma treatment.

[0253] In one embodiment, the surface treatment preferably includes coating treatment with a polymer containing a polar group. The coating treatment can improve the electrolyte impregnation and adhesion to the dried slurry. Examples of polar groups include carboxylic acid groups, hydroxyl groups, and sulfonic acid groups.

[0254] In one embodiment, the thickness (porous polyolefin resin substrate) is preferably 2 μm to 100 μm, more preferably 5 μm to 50 μm.

[0255] (Plastic non-woven fabric) Examples of the plastic nonwoven fabric include nonwoven fabrics made of only synthetic fibers.

[0256] Examples of synthetic fibers include polyolefin resins, polyester resins, acrylonitrile resins, polyamide resins, polyvinyl acetate resins, ethylene-vinyl acetate copolymer resins, acrylic resins, polyvinyl chloride resins, polyvinylidene chloride resins, polyvinyl ether resins, polyvinyl ketone resins, polyether resins, polyvinyl alcohol resins, diene resins, polyurethane resins, phenol resins, melamine resins, furan resins, urea resins, aniline resins, unsaturated polyester resins, alkyd resins, fluorine resins, silicone resins, polyamide-imide resins, polyphenylene sulfide resins, polyimide resins, polycarbonate resins, polyazine resins, polyesteramide resins, polyetheretherketone resins, polyparaphenylenebenzobisoxazole resins, polybenzimidazole resins, and ethylene-vinyl alcohol copolymer resins.

[0257] Examples of the polyolefin-based resin include polypropylene, polyethylene, polymethylpentene, ethylene-vinyl alcohol copolymer, and olefin-based copolymers.

[0258] Examples of the polyester resin include polyethylene terephthalate (PET) resin, polybutylene terephthalate (PBT) resin, polypropylene terephthalate (PPT) resin, polyethylene naphthalate (PEN) resin, polybutylene naphthalate resin, polyethylene isonaphthalate resin, and wholly aromatic polyester resins.

[0259] Examples of the acrylonitrile-based resin include polyacrylonitrile and copolymers of acrylonitrile and a (meth)acrylic acid derivative, vinyl acetate, and the like.

[0260] Examples of the polyamide-based resin include aliphatic polyamide, wholly aromatic polyamide, and semi-aromatic polyamide.

[0261] Examples of aliphatic polyamide include nylon and the like.

[0262] Examples of the wholly aromatic polyamide include poly(p-phenylene terephthalamide), poly(p-phenylene terephthalamide-3,4-diphenyl ether terephthalamide), and poly(meta-phenylene isophthalamide).

[0263] The "semi-aromatic polyamide" refers to a polyimide in which a part of the main chain of the aromatic polyamide is an aliphatic chain.

[0264] The plastic nonwoven fabric fibers may optionally contain fibers other than synthetic resin fibers.

[0265] Examples of fibers other than synthetic resin fibers include solvent-spun cellulose, fibrillated products of solvent-spun cellulose, regenerated cellulose, fibrillated products of regenerated cellulose, natural cellulose fibers, pulped products of natural cellulose fibers, fibrillated products of natural cellulose fibers, and inorganic fibers.

[0266] The mass % content (fibers other than synthetic fibers / nonwoven fabric) is preferably 50 mass % or less, more preferably 30 mass % or less, and further preferably 10 mass % or less.

[0267] Examples of the form (form) include single fibers and composite fibers.

[0268] "Single fiber" refers to a fiber formed of a single resin. "Conjugate fiber" refers to a fiber formed of two or more resins.

[0269] Examples of the form (composite fiber) include core-sheath type, eccentric core type, side-by-side type, island-in-the-sea type, segmented-orange type, and bimetallic laminated type (multiple bimetallic type).

[0270] In one embodiment, the average fiber diameter (plastic nonwoven fabric) is preferably 1 μm to 15 μm, more preferably 1 μm to 10 μm.

[0271] The “average fiber diameter” refers to the average value of the fiber diameters of 20 fibers randomly selected from a scanning electron microscope photograph.

[0272] In one embodiment, the average pore diameter (plastic nonwoven fabric) is preferably 1 μm to 20 μm, more preferably 3 μm to 20 μm, and further preferably 5 μm to 20 μm.

[0273] The "pore size" refers to the width of the gap between fibers. The "average pore size" refers to the average value of the pore sizes of 20 fibers randomly selected from a scanning electron microscope photograph.

[0274] In one embodiment, the thickness (plastic nonwoven fabric) is preferably 5 μm to 25 μm, more preferably 5 μm to 15 μm.

[0275] <Method for producing a separator for an electric storage device> Examples of the method for producing the electrical storage device separator include a method including a coating step of coating the electrical storage device separator slurry on a substrate and a drying step of drying the coated electrical storage device separator slurry.

[0276] (Coating process) Examples of the coating method include a coating method, a printing method, a transfer method, and a dipping method.

[0277] Examples of coating methods include a doctor blade, a rod, a reverse roll, a lip, a die, a curtain, and an air knife.

[0278] Examples of printing methods include flexographic printing, screen printing, offset printing, gravure printing, and inkjet printing.

[0279] Examples of the transfer method include roller transfer and film transfer.

[0280] Examples of the impregnation method include dipping.

[0281] (Drying process) Examples of the drying method include air drying, irradiation drying, and vacuum drying.

[0282] Examples of air drying include warm air drying, hot air drying, and low-humidity air drying.

[0283] Examples of irradiation drying include infrared irradiation drying, far infrared irradiation drying, and electron beam irradiation drying.

[0284] The drying temperature is preferably 40°C to 90°C, more preferably 50°C to 80°C.

[0285] The drying time is preferably 5 seconds to 3 minutes, more preferably 15 seconds to 2 minutes.

[0286] The manufacturing method (electrical storage device separator) may optionally include a pressing step.

[0287] Examples of the pressing means include die pressing and roll pressing.

[0288] The electrical storage device separator can be used as, for example, a battery separator, a non-aqueous secondary battery separator, a lithium ion battery separator, a sodium ion battery separator, and the like.

[0289] [Electrode stack for power storage devices] The present disclosure relates to an electric storage device separator / electrode stack having a dried product of the electric storage device slurry on an active material side of an electrode.

[0290] The electric storage device separator / electrode laminate is obtained by applying the electric storage device slurry onto an electrode and drying the resultant.

[0291] The production method (electrical storage device separator / electrode stack) includes, for example, a method including the following steps. (1) Step of coating a slurry containing an electrode material on a current collector (2) Step of drying the slurry containing the electrode material (3) Step of pressing the dried product of the slurry containing the electrode material (4) Step of applying the electrical storage device separator slurry onto the dried product of the slurry containing the electrode material (5) Step of drying the electrical storage device diaphragm slurry

[0292] Examples of the coating method, drying method and pressing method include the above-mentioned methods.

[0293] Uses (electrical storage device separator / electrode stack) include, for example, battery separator / electrode stack, battery separator / negative electrode stack, battery separator / positive electrode stack, non-aqueous secondary battery separator / electrode stack, non-aqueous secondary battery separator / negative electrode stack, non-aqueous secondary battery separator / positive electrode stack, lithium ion battery separator / electrode stack, lithium ion battery separator / negative electrode stack, lithium ion battery separator / positive electrode stack, sodium ion battery separator / electrode stack, sodium ion battery separator / negative electrode stack, sodium ion battery separator / positive electrode stack, etc.

[0294] [Electricity storage equipment] The present disclosure relates to an electric storage device.

[0295] In one embodiment, the electrical storage device includes the electrical storage device electrode.

[0296] In one embodiment, the electric storage device includes the electric storage device separator.

[0297] In one embodiment, the electrical storage device includes the electrical storage device separator / electrode stack.

[0298] (Electrolyte) The power storage device may optionally contain an electrolyte solution. Examples of the electrolyte solution include a solution in which a supporting electrolyte is dissolved in a non-aqueous solvent.

[0299] The non-aqueous solvents may be used alone or in combination of two or more.

[0300] Examples of the non-aqueous solvent include chain carbonate solvents, cyclic carbonate solvents, chain ether solvents, cyclic ether solvents, chain ester solvents, cyclic ester solvents, and acetonitrile.

[0301] Examples of the chain carbonate solvent include diethyl carbonate, dimethyl carbonate, and ethyl methyl carbonate.

[0302] Examples of the cyclic carbonate solvent include ethylene carbonate, propylene carbonate, and butylene carbonate.

[0303] Examples of the chain ether solvent include 1,2-dimethoxyethane.

[0304] Examples of the cyclic ether solvent include tetrahydrofuran, 2-methyltetrahydrofuran, sulfolane, and 1,3-dioxolane.

[0305] Examples of the chain ester solvent include methyl formate, methyl acetate, and methyl propionate.

[0306] Examples of the cyclic ester solvent include γ-butyrolactone and γ-valerolactone.

[0307] In one embodiment, the non-aqueous solvent preferably includes a combination of a cyclic carbonate and a chain carbonate.

[0308] The supporting electrolyte may be used alone or in combination of two or more.

[0309] Examples of supporting electrolytes include lithium salts. Examples of lithium salts include LiPF6, LiAsF6, LiBF4, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, (C2F5SO2)NLi, etc. In one embodiment, the supporting electrolyte preferably includes LiPF6, LiClO4, and CF3SO3Li.

[0310] In one embodiment, the non-aqueous electrolyte solution may optionally contain a coating film forming agent. The coating film forming agent may be used alone or in combination of two or more.

[0311] Examples of the film-forming agent include carbonates, cyclosulfides, sultones, and acid anhydrides.

[0312] Examples of the carbonate ester include vinylene carbonate, vinylethylene carbonate, vinylethyl carbonate, methylphenyl carbonate, fluoroethylene carbonate, and difluoroethylene carbonate.

[0313] Examples of alkyl sulfides include ethylene sulfide and propylene sulfide.

[0314] Examples of sultone include 1,3-propane sultone and 1,4-butane sultone.

[0315] Examples of the acid anhydride include maleic anhydride and succinic anhydride.

[0316] In one embodiment, the mass % content (film forming agent / electrolyte) is preferably 10 mass % or less, more preferably 8 mass % or less, further preferably 5 mass % or less, and particularly preferably 2 mass % or less.

[0317] Examples of the form (electricity storage device) include a cylindrical type in which an electrode sheet and a separator are spirally formed; a cylindrical type with an inside-out structure in which a plate electrode and a separator are combined; and a button type in which a plate electrode and a separator are stacked.

[0318] As a manufacturing method (electricity storage device), for example, there is a method described in Japanese Patent Application Laid-Open No. 2013-089437.

[0319] Examples of applications (electricity storage devices) include batteries, non-aqueous secondary batteries, lithium ion batteries, sodium ion batteries, and the like. Example

[0320] The present invention is specifically described below by way of examples and comparative examples. However, the above description and the following examples are not intended to limit the purpose of the present invention. The present invention is limited to the scope of the claims. Unless otherwise specified, the values ​​of parts, % and the like are by mass.

[0321] Example 1-1 In a reaction apparatus equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet pipe, 1278 g of ion exchange water, 220 g (1.55 mol) of a 50% acrylamide aqueous solution, 0.26 g (0.0026 mol) of dimethyl acrylamide, 0.40 g (0.0026 mol) of sodium methallyl sulfonate, 46.6 g (0.52 mol) of an 80% acrylic acid aqueous solution, and 27.4 g (0.52 mol) of acrylonitrile were added, and oxygen in the reaction system was removed by nitrogen gas, and the temperature was raised to 55° C. 0.17 g of ammonium persulfate and 10 g of ion exchange water were added thereto, and the temperature was raised to 80° C. for 3 hours to react. After the reaction was completed, 38.8 g (0.46 mol) of a 48% sodium hydroxide aqueous solution was added to obtain an aqueous solution of a storage device binder.

[0322] Unless otherwise specified, Example 1 and Comparative Example 1 described below were carried out in the same manner as Example 1-1 except that the procedures were changed as shown in the table.

[0323] [Table 1]

[0324] Example 2-1 300 g of ion-exchanged water was added to a reaction apparatus equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet pipe, and the oxygen in the reaction system was removed by nitrogen gas, and then the temperature was raised to 80°C. 340 g of ion exchange water, 770 g (5.4 mol) of 50% acrylamide aqueous solution, 5.1 g (0.03 mol) of N,N'-methylenebisacrylamide, and 8.7 g (0.06 mol) of sodium methallyl sulfonate were added to a 2 L beaker and stirred for 30 minutes to obtain a uniform solution A. 1.6 g of 2,2'-azobis-2-amidinopropane dihydrochloride (product name "NC-32" manufactured by Nihon Chemical Co., Ltd.) and 180 g of ion exchange water were added to a 300 mL beaker and stirred for 30 minutes to obtain a uniform solution B. Solution A and solution B were simultaneously added dropwise to the reaction apparatus over 3 hours to carry out a polymerization reaction, thereby obtaining an aqueous solution of a power storage device binder.

[0325] Unless otherwise specified, Example 2 and Comparative Example 2 described below were carried out in the same manner as Example 2-1 except for the changes shown in the table.

[0326] [Table 2]

[0327] The measurement conditions (weight average molecular weight, number average molecular weight, average radius of inertia) were as follows. · Measuring instrument: GPC (model: HLC-8420) manufactured by Tosoh Corporation Column: TSKgel guardcolumn PWXL 1 piece, TSKgel GMPWXL 1 piece (manufactured by Tosoh Corporation) · Eluent: Phosphate buffer (0.284 mol / L disodium hydrogen phosphate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) + 0.016 mol / L sodium dihydrogen phosphate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) aqueous solution, pH 8.0) Column temperature: 40℃ RI detector: Shodex RI-101 manufactured by Showa Denko K.K. MALS detector: DAWN HELEOS-II manufactured by WYATT Flow rate: 0.8ml / min ·Measurement concentration: 0.10 mass % (water-soluble polymer concentration) ·Measurement method: Measure after filtering. Filter: Cellulose acetate cartridge filter (manufactured by Tosoh Corporation, Microdiesk W-13-2, pore size 0.2 μm)

[0328] Example 3-1 200 parts of ion-exchanged water were added to a reaction apparatus equipped with a stirrer, a thermometer, a reflux condenser, a nitrogen inlet tube, and three dropping funnels, and the oxygen in the reaction system was removed by nitrogen gas, followed by heating to 80°C. Into a dropping funnel (1) were added 100 parts of acrylamide (49.5 mol%), 1 part of sodium methallylsulfonate (0.5 mol%) and 150 parts of ion-exchanged water to prepare a monomer mixed solution (I). Into a dropping funnel (2) were added 100 parts of acrylamide (49.45 mol%), 0.5 parts of sodium methallyl sulfonate (0.25 mol%), 0.6 parts of N,N'-methylenebisacrylamide (0.30 mol%) and 150 parts of ion exchange water to prepare a monomer mixed solution (II). Into the dropping funnel (3) were placed 1 part of a polymerization initiator (ammonium persulfate) and 180 parts of ion-exchanged water. Next, the solution was added dropwise from the dropping funnel (3) at a constant flow rate over about 3 hours. At the same time, the monomer mixed solutions (I) and (II) in the dropping funnels (1) and (2) were added dropwise in this order at a constant flow rate over about 1.5 hours. After the dropwise addition was completed, 50 parts of ion exchange water was added to prepare an aqueous solution of a power storage device binder.

[0329] Unless otherwise specified, Example 3 and Comparative Example 3 described below were carried out in the same manner as Example 3-1 except for the changes shown in the table.

[0330] [Table 3]

[0331] <Explanation of Abbreviations> ·AM: Acrylic amide (“50% Acrylic Amide” manufactured by Mitsubishi Chemical Co., Ltd.) DMAA: N,N-dimethylacrylamide (manufactured by KJ Chemicolor Co., Ltd., “DMAA”) ·MBAA: N, N'-methylenebisacrylamide AA: Acrylic acid (manufactured by Osaka Organic Chemical Industry Co., Ltd., "80% acrylic acid") ·AN: Acrylonitrile (manufactured by Mitsubishi Micron Co., Ltd., "Acrylonitrile") ·HEA: 2-Hydroxyethyl acrylate ("HEA" manufactured by Osaka Organic Chemical Industry Co., Ltd.) SMAS: Sodium methallyl sulfonate In the table, the numerical value of each component is mol %. The value of NaOH is a value relative to 100 mol % of the acidic group (COOH).

[0332] <Coating properties> The electrical storage device binder aqueous solution was applied to a plastic nonwoven fabric or a current collector copper foil using a bar coater. The nonwoven fabric or current collector copper foil after application was evaluated according to the following criteria. A: No coating streaks or white spots were generated. B: A small amount of coating streaks or white spots are produced. C: Many coating streaks or white spots are generated.

[0333] <Dispersibility> After the separator slurry or the electrode slurry was prepared, it was stored in an oven heated to 40° C. for 3 days. After the storage, the dispersibility of the slurry was visually evaluated according to the following criteria. A: Homogeneous paste as a whole, without liquid separation and no aggregates observed. B: Trace aggregates at the bottom of the container and slight liquid separation observed. C: Many aggregates at the bottom of the container and obvious liquid separation observed.

[0334] <Hygroscopicity> Dry 10 g of the aqueous solution of the power storage device adhesive through a circulating air dryer at 130 °C (product name “DRS420DA” manufactured by ADVANTEC) for 12 hours. Put the obtained solid into a polyethylene bag and crush it into about 5 mm × 5 mm with a wooden hammer. Put the crushed solid into a vacuum dryer (product name “VO-320P” manufactured by ADVANTEC), evacuate to a gauge pressure of 76 cmHg or less at 130 °C, and dry for 12 hours. Weigh about 1 g of the obtained test piece in a petri dish, put it into a thermo-hygrostat (product name “LH-113” manufactured by ESPEC), leave it standing at 65 °C and 60% humidity for 2 hours, and measure the mass. Hygroscopicity = { (mass after standing for 2 hours at 65 °C and 60% humidity) / (mass just after drying)} × 100 - 100 (%) A: Less than 20% B: 20% or more and less than 23% C: 23% or more

[0335] <Evaluation of the operation of the power storage device electrode> (1-1) Manufacture of the power storage device electrode paste Using a commercially available planetary mixer (product name “あわとり練太郎”, manufactured by SHINKI CO., LTD.), in a container dedicated to this mixer, mix 7 parts by mass (in terms of solid content) of the aqueous solution of the power storage device adhesive obtained in the example, 50 parts by mass of silicon particles with a D50 of 5 μm, and 50 parts by mass of natural graphite (manufactured by ITOU KOKUEN KOGYO CO., LTD., product name “Z-5F”). Add ion-exchanged water thereto so that the solid content concentration is 40%, and set this container in the above-mentioned mixer. Then, knead at 2000 rpm for 10 minutes and then defoam for 1 minute to obtain the power storage device electrode paste.

[0336] (1-2) Manufacture of the power storage device electrode On the surface of a current collector composed of a copper foil, uniformly coat the above-mentioned power storage device electrode paste by the doctor blade method so that the dried film thickness is 25 μm. After drying at 60 °C for 30 minutes, heat-treat at 150 °C / vacuum for 120 minutes to obtain an electrode. Then, perform pressing processing with a roll press so that the density of the film (electrode active material layer) is 1.5 g / cm3 , thus obtaining an electrode.

[0337] (1-3) Manufacturing of power storage devices In a glove box replaced with argon, the above-mentioned electrode was punched into a 16 mm diameter component and placed on a bipolar button battery (manufactured by Hohsen Co., Ltd., trade name "HS Flat Cell"). Next, a diaphragm punched into a 24 mm diameter polypropylene porous membrane (manufactured by CS TECH CO., LTD, trade name "Selion P2010") was placed, and after further injecting 500 μL of electrolyte in a way that does not enter the air, a commercially available metal lithium foil was punched into a 16 mm component and the outer body of the above-mentioned bipolar button battery was sealed with screws to assemble the storage device (lithium half-cell). The electrolyte used here is a solution in which LiPF6 is dissolved at a concentration of 1 mol / L in a solvent of ethylene carbonate / dimethyl carbonate = 3 / 7 (volume ratio).

[0338] The electrical storage device having the electrical storage device electrode produced using the electrical storage device binder aqueous solution of the example functioned without any problem.

[0339] <Operation evaluation of diaphragms for power storage devices> (2-1) Manufacturing of diaphragm slurry for power storage devices 5 parts by mass (in terms of solid content) of the storage device binder aqueous solution obtained in the example and 113 parts by mass of water were stirred and mixed, 100 parts by mass of boehmite (average particle size 0.8 μm) as non-conductive particles were added, and the mixture was dispersed and stirred at 15000 rpm for 60 minutes using a homogenizer (T25 digital ULTRA-TURRAX manufactured by IKA). Ion exchange water was further added to adjust the viscosity to prepare a storage device diaphragm slurry.

[0340] (2-2) Production of diaphragm: Lamination of diaphragm slurry layers (coating layers) A single-layer polyethylene separator substrate (PE substrate) having a width of 250 mm, a length of 200 mm, and a thickness of 6 μm was prepared by a wet process. The storage device separator slurry was applied to one surface of the separator using a gravure coater to a thickness of 3.0 μm after drying, and dried to obtain a storage device separator.

[0341] (2-3) Determination of peel strength A test piece with a width of 2 cm and a length of 10 cm was cut out from the obtained diaphragm, and the coated surface was fixed upward. Next, a tape with a width of 15 mm ("Selotep (registered trademark)" manufactured by Nichiban (Strain)) (according to JIS Z1522) was pressed on the surface of the ceramic layer of the test piece while sticking it, and then a tensile testing machine ("AGX-V" manufactured by Shimadzu Corporation) was used at 25°C to measure the stress when the tape was peeled off in a 180° direction at a speed of 30 mm / min from one end of the test piece. The measurement was performed 5 times. The greater the peel strength, the higher the adhesion strength between the substrate and the ceramic layer or the adhesion between the ceramic layers, and the more difficult it is to peel off the ceramic layer from the diaphragm substrate or the more difficult it is to peel off the ceramic layers from each other. In addition, the storage device having the storage device diaphragm functions without problems. Peel strength (adhesion) A: 40N / m or more B: less than 40N / m and more than 20N / m C: less than 20N / m

[0342] (2-4) Manufacturing of power storage devices In the production of the electric storage device in (1-3) above, the electric storage device is produced by the same method except that the separator produced above is used instead.

[0343] The electrical storage device having the electrical storage device separator produced using the electrical storage device binder aqueous solution of the example functioned without any problem.

Claims

1. An aqueous solution of an electrical storage device binder, The electrical storage device binder aqueous solution contains a water-soluble polymer, The water-soluble polymer comprises 10 mol% to 99.85 mol% of (meth)acrylamide units, 0.001 mol% to 20 mol% of alkyl (meth) acrylamide units and / or polyfunctional monomer units and Unsaturated hydrocarbon sulfonic acid unit: 0.001 mol% to 2.0 mol%.

2. A slurry for an electrical storage device, The electrical storage device slurry comprises a water-soluble polymer and water, The water-soluble polymer comprises 10 mol% to 99.85 mol% of (meth)acrylamide units, 0.001 mol% to 20 mol% of alkyl (meth) acrylamide units and / or polyfunctional monomer units and Unsaturated hydrocarbon sulfonic acid unit: 0.001 mol% to 2.0 mol%. The electrical storage device slurry according to claim 2 , comprising an electrode active material. The electrical storage device slurry according to claim 2 , comprising non-conductive particles. 5 . An electric storage device electrode comprising a dried product of the electric storage device slurry according to claim 2 or 3 on a current collector. 6 . An electric storage device separator comprising a dried product of the electric storage device slurry according to claim 2 or 4 on a substrate. 7 . An electrical storage device separator / electrode laminate comprising a dried product of the electrical storage device slurry according to claim 2 or 4 on an active material side of an electrode. 8 . An electric storage device comprising the electric storage device electrode according to claim 5 . 9 . An electric storage device comprising the electric storage device separator according to claim 6 . 10 . An electric storage device comprising the electric storage device separator / electrode laminate according to claim 7 .

Citation Information

Patent Citations

  • Binder for lithium ion battery electrode, paste for lithium ion battery negative electrode using the same and manufacturing method of lithium ion battery negative electrode

    JP2013089437A

  • Binder solution for lithium ion battery positive electrode, powdery binder for lithium ion battery positive electrode, slurry for lithium ion battery positive electrode, positive electrode for lithium ion battery, and lithium ion battery

    JP2018006333A